Mathematics
BernardineVarian
2016-09-26 09:30:09
Simplify the given expression below (7-3i) • (2-i)
ANSWERS
barbaradelk
2016-09-26 15:00:34

Foil it, 7 x 2, -3i x -i, 7 x -i, and -3i x 2. It would come to 14+3 i^2-7i-6i. i^2=-1, so it would be 14-3=11 and -7i-6i=-13i The answer is 11-13i

Cosborne1014
2016-09-26 15:01:49

(7−3i)(2−i) Rule:  [latex]left(a+bi ight)left(c+di ight)=left(ac-bd ight)+left(ad+bc ight)i[/latex] The values of the letters:  [latex]a=7,:b=-3,:c=2,:d=-1[/latex] Foil it:  [latex]left(7cdot :2-left(-3 ight)left(-1 ight) ight)+left(7left(-1 ight)+left(-3 ight)cdot :2 ight)i[/latex] Final answer: [latex]11-13i[/latex]

ADD ANSWER